Mapping suitable habitat and Anthropocene refugia for Ethiopian Guerezas: Insights for their conservation - Chala Adugna Kufa; Afework Bekele; Anagaw Atickem; Desalegn Chala; Diress Tsegaye; Torbjørn Ergon; Nils C. Stenseth; Dietmar Zinner (Global Ecology and Conservation)
Ethiopia is home to two subspecies of Colobus guereza, C. g. guereza and C. g. gallarum. Whereas C. g. guereza is listed as Least Concern by IUCN, the conservation status of C. g. gallarum is unclear, but according to a recent assessment, it will most likely be listed as Vulnerable, because of habitat loss due to agricultural expansion. We used climate data to model the habitat suitability for both taxa in a comparative study to identify suitable habitats within and outside of protected areas that may serve as Anthropocene refugia. Our ensemble models estimated 168,731 km2 as climatically suitable habitat for C. g. guereza and 69,542 km2 for C. g. gallarum with an overlap between the two taxa of 17.2 %. Areas that qualified as refugia, i.e., areas covered by forest, were 47,101 km2 (only 27.9 % of the total suitable habitat) and 8430 km2 (12.1 % of the suitable habitat) for C. g. guereza and C. g. gallarum, respectively. Of these, 39.8 % (C. g. guereza) and 53.7 % (C. g. gallarum) are within Ethiopia’s current protected area network. Given that potential Anthropocene refugia are found only partly within protected areas, conservation management should include this information when developing conservation strategies for both taxa. As the majority of suitable habitats for the two colobus taxa exist in non-forested regions, afforestation in these areas would be highly beneficial and is strongly recommended.